Market Response to Companies Sustainability Disclosure and Environmental Performance in Indonesia - Masayu Annisa Ihsani; Amrie Firmansyah; Riska Septiana Estutik (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to examine the impact of sustainability disclosure and environmental performance on market performance. Population of this study is non-financial companies listed in Indonesian Stock Exchange (IDX) from 2015 to 2019. Samples are 32 companies that participated in KLHK PROPER award (or 160 observations). Using multiple linear regression for panel data, this study found that sustainability disclosure is not associated with market performance, while environmental performance is positively associated with market performance. This study indicates that the Indonesia Financial Services Authority and the Ministry of Environment and Forestry need to improve the quality of policies related to sustainability used by companies in the Indonesian Capital Market.